Analysis of efficient building for energy conversion and storage using phase change material - Ahmed Raghad; C P Vandana; Reddy G. Vijendar; Sobti Rajeev; Chauhan Shilpi; Srivastava Arun Pratap (E3S Web of Conferences, 2024)
Building energy efficiency is now a top priority because of the major negative effects that may happen on the society, the economy, and the environment. In various parts of the world, several researchers have worked on ways of achieving methods that can use phasechange materials as thermal storage. This is because these technologies have the potential to greatly reduce energy consumption when combined with solar power. PCMs store thermal energy in ways quite different than ordinary construction materials. These materials make use of latent heat rather than sensible heat. Therefore, phase-changed materials possess a notable advantage over sensible heat thermal energy storage materials with respect to storing and releasing heat. As a result, this paper was concerned with exploring the possibility of building energy conversion and storage systems using phase change material.